2018
DOI: 10.1111/1365-2745.13089
|View full text |Cite
|
Sign up to set email alerts
|

Resident species with larger size metrics do not recruit more offspring from the soil seed bank in old‐field meadow vegetation

Abstract: 1. According to the traditional "Size Advantage" (SA) hypothesis, plant species with larger body size are expected to be more successful when competition is intense, that is, within severely crowded vegetation. Recent studies in old-field habitats, however, have shown that those species with greater numerical abundance as resident plants generally have a relatively small minimum reproductive threshold size (MIN), not a relatively large maximum potential body size (MAX).2. In this study, we test for a size adva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Inevitably, other factors, like available soil nutrients, can limit the height of the canopy by controlling which species can persist (Borer et al, 2014 ). Large species with large minimum reproductive size thresholds (Tracey & Aarssen, 2019 ) may be less likely to persist in low soil nutrient settings, and self‐thinning among tall plant species may create regular gaps, allowing light to reach smaller species (Schamp & Aarssen, 2014 ). Thus, nutrient limitation and competition among tall species may decrease the abundance of large plant individuals per area, simultaneously increasing light penetration and altering the importance of light as a previously limited resource.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inevitably, other factors, like available soil nutrients, can limit the height of the canopy by controlling which species can persist (Borer et al, 2014 ). Large species with large minimum reproductive size thresholds (Tracey & Aarssen, 2019 ) may be less likely to persist in low soil nutrient settings, and self‐thinning among tall plant species may create regular gaps, allowing light to reach smaller species (Schamp & Aarssen, 2014 ). Thus, nutrient limitation and competition among tall species may decrease the abundance of large plant individuals per area, simultaneously increasing light penetration and altering the importance of light as a previously limited resource.…”
Section: Discussionmentioning
confidence: 99%
“…There is also little evidence of deterministic organization of species according to size in herbaceous communities (Schamp et al, 2008 ). Recent research has shown that species with larger body size in fact do not dominate neighborhood biomass production in old‐field vegetation (Tracey et al, 2017 ), nor do they recruit more offspring from the soil seed bank (Tracey & Aarssen, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inevitably, other factors, like the available soil nutrients, can limit the height of the canopy by controlling which species can persist (Borer et al 2014). Large species with large minimum reproductive size thresholds (Tracey and Aarssen 2019) may be less likely to persist in low soil nutrient settings and self-thinning among tall plant species may create regular gaps, allowing light to reach smaller species (Schamp and Aarssen 2014). Thus, nutrient limitation and competition among tall species may decrease the abundance of large plant individuals per area, simultaneously increasing light penetration and altering the importance of light as a previously limited resource.…”
Section: Testing Hypotheses Related To Species Size and Light Penetrationmentioning
confidence: 99%
“…There is also little evidence of deterministic organization of species according to size in herbaceous communities (Schamp et al 2008). Recent research has shown that species with larger body size in fact do not dominate neighbourhood biomass production in old-field vegetation (Tracey et al 2017), nor do they recruit more offspring from the soil seed bank (Tracey and Aarssen 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Key plant functional traits such as seed mass, maximum plant height, specific leaf area (SLA) and reproductive/vegetative biomass ratio (reproductive ratio, hereinafter) are clearly connected to the main ecological processes that determine community and population assembly. For example, large‐seeded species have competitive (Freckleton & Watkinson, 2001; Rees, 1995) and establishment advantages (Freckleton & Watkinson, 2001; McConnaughay & Bazzaz, 1987; but see Tracey & Aarssen, 2019) compared with small‐seeded species. The initial seedling size is positively correlated with seed size (Leishman et al, 2000), and larger seedlings are usually favoured under competitive or drought conditions (Leishman & Westoby, 1994).…”
Section: Introductionmentioning
confidence: 99%